Detection of Inclusions and Degradation in Injection-Molded Thermoplastics - Kim, Sun Kyoung; Bae, Seulgi; Sung, Jihyun; Choi, Shinbi (Journal of Composites and Biodegradable Polymers, 2019)
This work suggests a formal procedure to identify inclusions and anomalies in injection molded specimens. To find a suitable procedure, experiments with actual molded specimens have been tested. The specimens were injection molded blow preform of PET with inclusions and the PET preform degraded intentionally by controlling the residence time. By microtoming the inclusions have been exposed to the surface and then they have been analyzed by XRD, XRF, FTIR and DSC. Based on the results, this study have proposed a simple protocol for identifying visually observable foreign or unwanted substances. It starts with optical microscopy followed by SEM/EDS. Based on the result and amount of the inclusions, the procedure move onto conventional FTIR or micro-IR test. The XRF can be of aid especially when the inclusion is inorganic.